In vitro evidence for gut hormone stimulation release and dipeptidyl-peptidase IV inhibitory activity of protein hydrolysate obtained from cuttlefish (Sepia officinalis) viscera. (December 2015) - Cudennec, Benoit; Balti, Rafik; Ravallec, Rozenn; Caron, Juliette; Bougatef, Ali; Dhulster, Pascal; Nedjar, Naïma
Abstract: Two cuttlefish ( Sepia officinalis ) viscera protein hydrolysates were obtained with different enzymes extracted from cuttlefish and smooth hound ( Mustellus mustellus ). Their ability to stimulate the secretion of cholecystokinin (CCK) and glucagon-like peptide 1 (GLP-1), using the enteroendocrine STC-1 cell line, and to inhibit the DPP-IV activity during a simulated gastrointestinal digestion was assayed. The physico-chemical parameters of hydrolysates and their effects on intestinal cell viability were also determined. The hydrolysate obtained with cuttlefish enzymes (CVPH1) appeared to be the most promising for all assessed bioactivities. Thus CVPH1 was able to stimulate CCK and active GLP-1 releasing activities of enteroendocrine cells without any cytotoxicity and to inhibit DPP-IV activity. Moreover, these actions were enhanced after gastrointestinal digestion and CVPH1 was also able to inhibit the intestinal DPP-IV activity of Caco-2 cells. These very promising findings highlight, via two different mechanisms, the positive effect of CVPH1 on GLP-1 actions. Highlights: In Tunisia, cephalopods industry processing generates wastes causing environmental pollution and commercial loss. Cuttlefish hydrolysates were able to stimulate gut hormone release in enteroendocrine cells and to inhibit DPP-IV activity. Hydrolysates bioactivities assessed after GI digestion were enhanced by the action of proteases compared with raw byproduct. This cuttlefish byproduct hydrolysate will be useful in obesity and T2D management research.